PERANCANGAN DAN PENGEMBANGAN SISTEM DETEKSI MUSUH NIRKABEL MENGGUNAKAN ESP32, SENSOR MMWAVE C4001, DAN MODUL HC-12 SEBAGAI PENGGANTI POSISI PENDENGAR DI BASIS OPERASI MAJU (FOBS) - Gunawan, Ardiansyah; Hidayat, Bayu Ramdhani; Saputra, Jeki (Jurnal Elkasista, 2024)
: Security and effectiveness in detecting enemy presence in operational areas are critical to the success of military missions. This research designs and develops an enemy detection system based on the ESP32 microcontroller integrated with the mmWave C4001 sensor and the HC-12 wireless communication module, as an alternative to conventional listening posts in Forward Operating Bases (FOBs). The system is designed to detect human movement in real-time using high-frequency microwave signals capable of detecting presence without direct physical contact. The HC-12 module is used to wirelessly transmit detection data to a remote receiving post. The methodology includes hardware and software design, sensor function testing, and communication range measurement. Test results show that the system is capable of detecting human presence at a distance of up to 6 meters with high accuracy and transmitting data stably up to 100 meters in unobstructed conditions. The system also has low power consumption, making it suitable for field deployment. The conclusion of this research is that the designed system is effective as a portable and automated alternative to traditional listening posts. Future development is suggested to focus on expanding the system into a mesh-based detection network with multiple nodes to cover a wider area around the Forward Operating Base (FOB). Keywords: ESP32, mmWave C4001, HC-12, enemy detection, listening post, wireless system